Metabolomics and transcriptomics analyses of sugarcane variety SP80-3280 throughout development in the field - Wijma, Maryke (2020)
Sugarcane (Saccharum sp.) is considered one of the world\'s most efficient crops in the conversion of solar to chemical energy in the form of sugar and biomass, and it has mostly been exploited as a primary source for the production of sugar and bioethanol. Yield improvements are required to meet the increasing demands for sugar and bioethanol production; however, it is necessary to understand how sugarcane perceives and responds to changes in its external environment to meet these demands. Previous work from the group observed that precipitation and temperature influence SP80-3280\'s yield and maturation profile. Field experiments showed that sugarcane can support early phase water deficit by continuing photosynthate production and carbon assimilation in the form of fiber production, specifically producing thicker culms, instead of accumulating sugar. Yield is a complex trait that needs integrated approaches for being studied. We developed and took a systems biology approach integrating data from the sugarcane metabolome and transcriptome to verify if and which pathways are altered during the growth and maturation cycle of this crop. We developed an analytical and statistical pipeline for conducting untargeted metabolomics studies and integrating it in an unsupervised manner with transcriptomics data, thus highlighting the importance of integration when working with highly complex and heterogeneous datasets. We discuss four main pathways associated with SP80-3280\'s development: pentose phosphate pathway; phenylalanine, tyrosine and tryptophan biosynthesis; flavonoid biosynthesis; and phenylpropanoid biosynthesis, mostly active in the main source (leaf) and sink (mature internode) tissues. Candidate genes (CAD, PER, PAL, F3H) within these pathways are identified as possible targets for further studies to better understand the different developmental profiles and their carbon demand. This study also sheds light on the metabolomics and transcriptomics differences between four different anatomical tissues. Additionally, economically and agronomically valuable compounds, such as phenolics and glucosinolates were identified which contributed to the knowledge gaps regarding the sugarcane metabolome and suggested new uses for currently poorly utilized parts of the sugarcane plant.